NALAR HISTORIS PERPOLITIKAN KAUM HAWA MASA NABI MUHAMMAD SAW - Wahyu Iryana (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2019)
This paper tries to portray the role of women in the socio-political dimension in the era of the early arrival of Islam Islam is a tolerant religion that has given birth to a number of figures of brave women.. Just mention Khadijah Binti Khuwalid, Fatimah Az Zahra, Shafiyyah Binti Abdul Muthollib, Lubabah, Umul Fadhal Binti Harits, Asma Binti Amis (Wife Jafar), Fatimah Binti Khatab (Wife Said Bin Zaid), Sumayyah fighters women who sacrificed to make the nation proud and religion. For Islam, women are not only used as the secondline of life but rather, women can color the joints of life in a wider scope. So prominent is the role of women in the time of Prophet Muhammad SAW, that they were able to give up property for the glory of Islam they deserve to be called "de leidster van het verzet". Leaders of resistance like Summayah. The research method uses a descriptive approach by processing data into a writing with historical flow. The results of the study have been found that since Islam came Women have contributed to everything, starting from the economy as entrepreneurs, politicians, war fighters, housewives, and propagators of religious preaching. Tulisan ini mencoba memotret peran perempuan dalam dimensi sosial politik di era awal kedatangan Islam. Islam adalah agama toleran yang telah melahirkan sejumlah tokoh perempuan pemberani. Sebut saja Khadijah Binti Khuwalid, Fatimah Az Zahra , Shafiyyah Binti Abdul Muthollib, Lubabah, Umul Fadhal Binti Harits, Asma Binti Amis   (Istri Jafar), Fatimah Binti Khatab (Istri Said Bin Zaid), Sumayyah  pejuang wanita yang rela berkorban untuk mengharumkan nama Bangsa dan Agama. Bagi Islam Perempuan sesungguhnya bukan hanya dijadikan secondline kehidupan saja melainkan dari itu, Perempuan bisa mewarnai sendi-sendi kehidupan dalam cakupan yang lebih luas. Begitu menonjolnya peranan perempuan di masa Nabi Muhammad SAW., hingga mampu merelakan harta benda untuk kejayaan Islam mereka layak dsebut“de leidster van het verzet”. Pemimpin perlawanan seperti halnya Summayah. Metode penelitian menggunkan pendekatan deskriptif dengan mengolah data menjadi sebuah tulisan dengan alur historis. Hasil dari penelitian diperoleh bahwa sejak Islam datang Perempuan sudah memberikan kontribusinya di segala hal, dari mulai ekonomi sebagai pengusaha, politikus, pejuang perang, ibu rumah tangga, dan penyebar dakwah agama.